Urinary screening to determine the positivity of DMB and high volt age electrophoresis of mucopol ysaccharidosis in suspected metabolic disorders children in HUSM - Omar, Julia (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2013)
i11troductio11: Mucopolysaccharidoses (MPS) is a disease of inborn errors of metabolism (!EM). It constitutes a large and heterogenous subgroup among the lysosomal storage diseases. For the detection of this disease, urinary glycosaminoglycan (GAG) is measured by dimethlmethylene blue (DMB) assay and high resolution electrophoresis (I-IRE) is done to characterize the different types of MPS. Objective: To screen for MPS in all urine samples suspected of inborn errors of metabolism sent to the metabolic laboratory from 1998 to 2008 and to look into the association between the positivity of DMB assay and I-IRE in the same sample Group Met/rod: All urine samples sent to the metabolic laboratory that fulfilled the inclusion criteria were analyzed for GAG and were further subjected to I-IRE. Measurement of observed agreement using Cohen's kappa coefficient (k) was used for the association between both DMB and I-IRE method. Results: A total of 134 urine samples were obtained however only 90 samples were analyzed. 28 (31.1 %) of the samples had normal GAG levels, 59 (65.6%) had GAG levels between 1-2 folds above normal limits and 3 (3.3%) samples had more than 2 folds increment above the normal limits for age. Three samples showed abnormal bands when subjected to I-IRE. Poor association between both methods (k = 0.027) was observed. Co11clusio11: This study shows that all samples with high index of suspicion ofMPS and elevated values of GAG of two folds or more should be subjected to I-IRE. Characterization of MPS through I-IRE gives the clinician some presumptive diagnosis and prognosis in managing these patients.